Unusual imaging appearance of unicystic ameloblastoma - Lakshmi Kavitha Nadendla (Wolters Kluwer Medknow Publications, 2012)
Unicystic ameloblastoma (UA) refers to those cystic lesions that show clinical, radiographic, or gross features of a mandibular cyst, but on histologic examination show a typical ameloblastous epithelium lining part of the cystic cavity, with or without luminal and/or mural tumor growth. It accounts for 5-15% of all intraosseous ameloblastomas. We report a case of UA in a 35-year-old female with an unusual large multilocular (tennis racket) appearance on the right body of mandible and illustrate the importance and complexity of differential diagnosis with a brief review of recent literature.